Development of portable power supply ( Solar Briefcase) - Haliff Anas bin Anuar (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2015)
Nowadays solar system is widely used as a renewable energy, whether on-grid or off-grid in the electrical system. The energy is collected from the sunlight by the solar panel then being used as a power supply. There are no ongoing electrical bills, no reliance on a power socket and a free everlasting source of energy that does not harm the planet. This product will be designed as a briefcase. The idea is to make the solar system as a portable renewable energy that can be used anywhere and able to bring it easily. In other applications, the objective is to create an AC voltage when only a DC voltage source is available. The focus of this project is on the inverters that produce an AC output from a DC input. In the other word, the inverter is the main circuit that converting 12Vdc from the rechargeable battery input to 240Vac output. The rechargeable battery can be charged by the solar panel or optionally by the wall socket. Besides that, the level of the battery used inside the briefcase will be indicated by the LED for alerting user whether the supply full charged or low level condition. In conclusion, this project will be specially created for the user to do something that needed AC/DC electrical supply below 100W without using the power in their home directly.